PUBLIC RELATIONS MANAGEMENT IN BUILDING A BRANDING IMAGE OF BOARDING SCHOOLS - Maula, Rofikatul; Hefniy, Hefniy; Baharun, Hasan (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Public relations management is essential in building an educational institution's image. The image of an excellent educational institution can increase the attractiveness and trust of the community, parents of students, and prospective students. In this article, the author discusses how public relations management can help build the image of educational institutions. Some recommended strategies and tips have a strategic plan, using social media well, having an extensive network, and being responsive to requests and issues. The research method in this article uses a qualitative case study type method. By implementing excellent and integrated public relations management, educational institutions can build a good image and increase public trust in educational institutions. This can help educational institutions to attract the interest of prospective students and parents and improve the quality of education provided.